Understorey bird species composition in primary and logged forest with special reference to insectivorous/frugivorous birds in Sungai Lalang forest reserve, Selangor / Mohamed Zakaria and Zamri Rosli - Zakaria, Mohamed; Rosli, Zamri (2002)
In Malaysia, the major cause of forest disturbance is through logging activities. Logging is known to affect the distribution and abundance of forest food resources, which are necessary for wildlife existence. The objective of the study is to determine bird species composition with reference to insectivorous /frugivorous group in two forest types; primary forest (VJR) and 10-year-old-loggedforest (Compartment 33) of Sungai Lalang Forest Reserve, Selangor. The method used was mist netting. A total of 58 individuals of understorey insectivores/ frugivores birds were recorded in primary forest and 106 individuals were recorded in 10-year-old logged forest. In terms of species composition 10 species of understorey insectivore/ frugivore were recorded in primary forest whereas 16 species were recorded in 10-year-old logged forest. It was found that the number of individuals of understorey insectivores/frugivores birds were higher in 10-year-old logged forest compared to primary forest. Therefore, in conclusion, in terms of species composition, logged forest contained higher number of bird species than primary forest.